2023
DOI: 10.3390/diagnostics13071345
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes, Immunophenotyping and Immunohistochemical Findings in a Cohort of Pregnant Patients with COVID-19—A Prospective Study

Abstract: (1) Background: SARS-CoV-2 infection during pregnancy could determine important maternal and fetal complications. We aimed to prospectively assess placental immunohistochemical changes, immunophenotyping alterations, and pregnancy outcomes in a cohort of patients with COVID-19; (2) Methods: 52 pregnant patients admitted to a tertiary maternity center between October 2020 and November 2021 were segregated into two equal groups, depending on the presence of SARS-CoV-2 infection. Blood samples, fragments of umbil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Lastly, it is worth mentioning that part of our study period (2019-2022) overlapped with the coronavirus disease 2019 (COVID-19) pandemic. Though COVID-19 infection status was not assessed in our study, previous studies have indicated no statistically significant difference between COVID-19 positive and COVID-19 negative patients regarding pregnancy outcomes (such as neonatal intensive care unit admission and stillbirth) [35,36], while others suggest an association between specific COVID-19 variants and various pregnancy complications (such as PTB) [37].…”
Section: Discussionmentioning
confidence: 61%
“…Lastly, it is worth mentioning that part of our study period (2019-2022) overlapped with the coronavirus disease 2019 (COVID-19) pandemic. Though COVID-19 infection status was not assessed in our study, previous studies have indicated no statistically significant difference between COVID-19 positive and COVID-19 negative patients regarding pregnancy outcomes (such as neonatal intensive care unit admission and stillbirth) [35,36], while others suggest an association between specific COVID-19 variants and various pregnancy complications (such as PTB) [37].…”
Section: Discussionmentioning
confidence: 61%
“…Artificial intelligence and risk stratification have been gaining more interest in the field of predictive medicine, and they have been frequently used in imaging data modeling in recent years [41][42][43][44][45][46]. Moreover, the correct reporting of positive circumferential margin on MRI has been the subject of debate.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that patients with urosepsis had an increased likelihood of premature rupture of membranes (aOR: 5.59, 95%CI: 2.02-15.40, p < 0.001) and preterm birth (aOR: 2.47, 95%CI: 1.15-5.33, p = 0.02). The role of urinary infections in the determinism of preterm birth is well established, and immunosuppressive conditions favor the development of severe forms of infection, as we determined in this study [41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%